Pengembangan Potensi UMK Desa Dutohe Barat Berbasis Bahan Lokal Pemanfaatan Daun Kelor (Moringa oleifera) dalam Meningkatkan Kesehatan Masyarakat - Wiwin Rewini Kunusa; Mangara Sihaloho; La Ode Aman; Inrawani Inrawani; Suci Damayanti; Nur Isty Fidya; Meylani Frisilia; Zulfa K Muslimin; Moh. Fajri (Universitas Negeri Gorontalo, 2022)
Village building activities or Thematic Real Work Lectures (KKNT) are expected to be able to hone soft partnership skills, cross-disciplinary/scientific collaboration (cross-competencies), and student leadership in managing development programs in rural areas. The purpose of this activity is to increase public knowledge about the processing of Moringa leaves and their waste into products with high economic value. This is expected to encourage the realization of developed and independent villages, as well as village and city cooperation through sustainable rural development. Apart from that, it also encourages the growth and development of investment in villages and rural areas, underdeveloped areas, and transmigration areas.